(3JGQjN MhGOK GdReGf hCfHGFg hhajGJ GdCcGHQ hGdCYjGf ef CHfGFgs - (3eMeO Hf EHQGgje Hf CHj HcQ Hf EHQGgje Hf YHO GdYRjR GdLRQj GdOeTbqj, TeS GdOjf, CHh YHO Gddg,J (B739 (3g` s
(3ChdgG (B:s
(3ESJgdJ SJI KeGf hSJeGFI hGdSdWGf Gdedc GdYGOd hEHfg Gdedc GdeYXe fGRdkG HGdeNje Ydi GdWhQ heYgeG HGdYSGcQ s
(3BNQgG (B:s
(3hjfJgi HGdMOjK Yf Gdedc GdeXaQ Hbhdg (B: (3hCUdM eG EVWQH ef GdCehQ hYGO dbUO GdOjGQ GdeUQjI abJd bHd hUhdg EdjgG s
(3GTJedJ GdfSNI Ydi MhGOK ef (B608 (3Edi SfI (B658 (3cJH ai BNQ GdeNWhWI HNW eZGjQ MOjK BNQ GdLRA GdKGfi ef JGQjN MhGOK GdReGf hCfHGFg JCdja GdMGdaX TeS GdOjf eMeO GdLRQi GdOeTbi jJdhg ai Chd GdKGdK PcQ ebJd GdSdWGf Gdedc GdeRaQ Sja GdOjf bXR hfHPg ef CNHGQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(194 (3b(B) s
Keywords: (3GdJGQjNs